2018
DOI: 10.3390/jcm7110431
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Albuminuria and Intraoperative Chloride Load: Predictors of Acute Kidney Injury Following Major Abdominal Surgery

Abstract: Background: Postoperative Acute Kidney Injury (AKI) is a common and serious complication associated with significant morbidity and mortality. While several pre- and intra-operative risk factors for AKI have been recognized in cardiac surgery patients, relatively few data are available regarding the incidence and risk factors for perioperative AKI in other surgical operations. The aim of the present study was to determine the risk factors for perioperative AKI in patients undergoing major abdominal surgery. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Thirteen studies were prospective, 16,18,19,21,44–52 and 15 studies were retrospective 17,20,22,23,53–63 . Twenty-four studies enrolled a total of 29 445 patients undergoing cardiovascular surgery 16,18,19,21–23,44,45,47–61,63 .…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies were prospective, 16,18,19,21,44–52 and 15 studies were retrospective 17,20,22,23,53–63 . Twenty-four studies enrolled a total of 29 445 patients undergoing cardiovascular surgery 16,18,19,21–23,44,45,47–61,63 .…”
Section: Resultsmentioning
confidence: 99%
“…Suetrong et al [6] suggested that the maximum serum chloride level (i.e., ≥ 110 mmol/L) and an increase ≥ 5 mmol/L within 48 hours after ICU admission due to severe sepsis or septic shock were the predominant factors associated with the development of AKI. Another study conducted by Marouli et al [12] suggested that a high intraoperative chloride load (i.e., > 500 mEq) played a significant role in the development of AKI within 48 hours after major abdominal surgery. In a prospective ICU study, a lesser intravenous chloride supply was associated with significant reduction in the worst stages of AKI and the requirement for RRT.…”
Section: Discussionmentioning
confidence: 99%
“…These harmful effects of hyperchloremia have largely been investigated in the context of chloride-rich solution resuscitation, which has been found to have a detrimental impact on kidney function [10,11]. However, the relationship between hyperchloremia and AKI has been investigated only in native (i.e., not transplanted) kidneys, in the context of clinical conditions such as sepsis, subarachnoid hemorrhage, and abdominal surgery [5,6,7,8,12].…”
Section: Introductionmentioning
confidence: 99%
“…The following are excluded: 10 duplicate records, 8 conference abstracts, 8 case reports, 6 notes, letters, or editorials, 18 reviews, 1 non-surgical record, 9 non-preoperative proteinuria records, 25 non-postoperative AKI records, 20 unrelated records, 1 record with children as participants, 3 nephrectomy records, and 4 records are excluded for other reasons. Therefore, we identify 10 records including 11 studies totally and report studies for our meta-analysis [14][15][16][17][18][19][20][21][22][23][24] (Figure 1).…”
Section: Study Characteristicsmentioning
confidence: 99%